Clinical Impact of DIEP Flap Perforator Characteristics – A Prospective Indocyanine Green Fluorescence Imaging Study. Issue 8 (August 2020) - Anker, Alexandra M.; Prantl, Lukas; Strauss, Catharina; Brébant, Vanessa; Baringer, Magnus; Ruewe, Marc; Vykoukal, Jody; Klein, Silvan M.
Summary: Background: The question to what extent perfusion in deep inferior epigastric perforator (DIEP) flaps depends on specific perforator characteristics has been raised. Anatomical studies and previous clinical trials focussing on DIEP flap perfusion resulted in discrepancies. This prospective study investigates how perforator row, number and diameter affect DIEP flap microperfusion via Indocyanine Green (ICG) fluorescence angiography. Methods: The fractional weight of insufficiently perfused flap tissue in Zone 4 related to the total DIEP flap weight was measured based on ICG fluorescence angiography and defined as Zone 4 %. As a surrogate for overall DIEP flap perfusion, Zone 4 % was assessed according to the row, number and diameter of perforators included in the flap. Results: In 42 unilateral DIEP flap breast reconstructions, neither medial (33.6 ± 14.2 %) /lateral perforator row (29.9 ± 7.5 %, p = 0.683) nor the parameter perforator number (single perforator 31.5 ± 14.4 %, two perforators 30.2 ± 10.2 %, p = 0.727) had a statistically significant effect on flap tissue availability as measured via Zone 4 % . A negative correlative trend between perforator diameter and Zone 4 % (r = -0.096, p = 0.588) was observed. Conclusion: Zone 4 % provides a novel method for an objective assessment of DIEP flap perfusion. Medial/lateral row selection and other perforator properties ( number, diameter ) within the standard ranges, did not affect Zone 4 % as indicated by ICG fluorescence angiography.